[Au7Ag9(dppf)3(CF3CO2)7BF4]n: a linear nanocluster polymer from molecular Au7Ag8 clusters covalently linked by silver atoms. Issue 86 (14th October 2019) - Wen, Zhao-Rui; Guan, Zong-Jie; Zhang, Ying; Lin, Yu-Mei; Wang, Quan-Ming
Abstract : A unique nanocluster polymer consists of the building block of Au7 Ag8 clusters joined together to form a one-dimensional linear chain. Abstract : We report the total structure determination of a covalently bonded nanocluster polymer [Au7 Ag9 (dppf)3 (CF3 CO2 )7 BF4 ] n (1 ). This features a one-dimensional linear chain, consisting of unique molecular building blocks, Au7 Ag8 (dppf)3 (CF3 CO2 )7 clusters, which are linked together by Ag–O bonds rather than Au–Au interactions or bidentate organic bridges as previously reported.